Adsorption Behavior of Clarified Sugarcane Juice - Prasad, K.; Sharma, H.K. (Asian Journal of Chemistry, 2010)
Colouring substances in sugarcane juice are undesirable impurities and are classed as non-sugar impurities. The present paper deals with the purification of colouring impurities through the adsorption process using activated charcoal as an adsorbent. The study indicates that an effective purification of CSJ (clarified sugarcane juice) can be obtained at a concentration of 0.04 g carbon/g CSJ for 25 min carbon-CSJ contact time at an ambient temperature (30 ± 2°C) in purification process.